Clinical outcomes of primary Latarjet technique in recurrent shoulder dislocation using BioLatarjet® LCS cannulated flat head screws - N., Prashanth B.; M., Mahesh (International Journal of Research in Orthopaedics, 2023)
Background: The Latarjet technique is an effective procedure that reconstructs and augments the glenohumeral joint instability. It improves stability by increasing the glenoid width and using the sling effect. The aim of the study was to assess the functional outcomes of the primary Latarjet treatment with BioLatarjet® LCS cannulated flat head screws in cases of recurrent shoulder dislocation. Methods: In this retrospective study, 30 patients were treated with the primary Latarjet technique. Rowe score, visual analog scale (VAS), Quebec back pain disability scale (QDS), and, American shoulder and elbow surgeon score (ASES), and range of motion (ROM) were evaluated in the selected population at the time point of 6-week, 3-month, and 6-month after surgery for the determination of the functional outcomes in them. Results: The results showed that all patients had excellent or good functional outcomes with significant improvements in Rowe score, VAS score, QDS, and ASES scores (p<0.0001). The ROM in patients for forward elevation, cross body adduction, external rotation by side of body/neutral, and internal rotation by side of body/neutral were related to better clinical outcome and less movement of recurrent instability with optimal graft placement. Conclusions: These findings have clinical significance in that they demonstrate the effectiveness of the Latarjet technique in improving stability without significantly increasing the risk of complications. The BioLatarjet® LCS cannulated flat head screws were found to be safe and efficient for primary Latarjet surgeries, providing appropriate graft healing and a low recurrence of instability, with a good return-to-sports rate.